Predictors of Musculoskeletal Disorders Among Teachers: An Exploratory Investigation in Malaysia - Ng Yi Ming; Peter Voo Su Kiong; Ismail Maakip (Canadian Center of Science and Education, 2020)
Purpose: The present study aimed to examine the prevalence and gender differences in MSDs among teachers, as well as the interaction of associated predictor .In addition, another aim of the study was to investigate the contribution of these predictors, which have not been examined thoroughly particularly in Malaysia. Methodology: A cross-sectional study was employed in this study. A questionnaire was used to measure physical factors, psychosocial factors, workload, work-life balance, general well-being, and MSDs levels among primary school teachers (N=460) from 10 primary schools in Kota Kinabalu. Findings: The prevalence of MSD in the past 6 months was 61.7% (95% CI: 57.4% – 65.9%). The present study findings also indicated that there were significant gender differences in MSDs between female and male teachers (t = 1.04, p< .05). Hierarchical multiple regression was conducted to examine a range of predictors related to MSDs. Physical factors (ß = .17, p<0.05). Multiple regression was used for a variety of predictors that are associated with MSD. Physical factors (ß = .17, p<0.05), psychosocial factors (ß = -.14, p<0.05), and general well-being (ß = .43, p<0.01) are significantly associated with MSD in Malaysian primary school teachers. Overall, model statistic result was F (3, 276) = 36.730, p=0.001, R² = .45 and adjusted R² = .435. The model explained 44.7% (r= 0.67) of the variance in MSD discomfort. Conclusion: The studies concerning MSDs among teachers revealed the need for a significant effort, not only to examine the risk factors but also to develop interventions to minimize MSDs for those in the teaching profession.